Risk of pregnancy and external validity in clinical trials of emergency contraception. Issue 3 (1st July 2006) - Westley, Elizabeth; Bigrigg, Alison; Johnston, Karen; Spiers, Aileen; Webb, Anne; Haskell, Sue; Loftus-Granberg, Becca; Blanchard, Kelly; Abuabara, Katrina; Ellertson, Charlotte; Sorhaindo, Annik
Abstract : Objectives: To compare women who enrol in emergency contraception (EC) trials to those who decline and to understand why eligible women decline to participate. Methods: Data were collected from all women seeking EC ( n = 5787) at three clinics in the USA and UK during a period of nearly 1 year (from September 1997 to August 1998). The main outcome measures were pregnancy risk calculated by adjusted cycle day of ovulation. Results: Enrolled and non-enrolled women had similar mean ages and similar mean cycle lengths. However, the enrolled and non-enrolled groups were different with respect to adjusted cycle day of unprotected sexual intercourse (UPSI), the regularity of their cycles, recent hormone use, breastfeeding, the number of other acts of UPSI they had engaged in during the same cycle, and their willingness to participate in the study. Expected pregnancy risk among enrolled patients was higher than among non-enrolled EC seekers (6.5% vs 5.0%, p <0.001, calculated using Dixon conception probabilities, and 5.4% vs 4.6%, p = 0.086, calculated using Trussell conception probabilities). Unwillingness to take part in the study was the most common reason women did not enrol in the trial. Otherwise-eligible women most often declined to enrol because they were concerned about the effectiveness of the trial regimen. Conclusions: Women in EC trials are likely to face higher pregnancy risk than the general population. Clinical trials might overestimate the number of pregnancies averted by treatment because the number of expected pregnancies in trial populations is not representative of the population of all EC seekers. This information could be useful in projecting the public health impact of expanded EC access.